re Effect Of Enterprises’ Fundamental Factors And Systematic Risk On Stock Returns - labbeik, kevin; Baridwan, Zaki; Saraswati, Erwin (Publikasi Indonesia, 2023)
This study aims to determine the influence of fundamental factors of companies and systematic risks on stock returns. The type of data used in this study is secondary data. The data is obtained from annual reports and financial reports sourced from www.idx.co.id. The population used in the study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2021. The samples used in this study were 42 manufacturing companies listed on the IDX that met the criteria. Data were analyzed using multiple linear regression method. The results of this study indicate that the enterprise's fundamental factors affect stock returns. There are significant differences in the variable size of enterprise asset sizes before and during the Covid-19 pandemic. However, there were no significant differences in liquidity variables, debt to equity ratio, return on equity, earnings per share, price earnings ratio and systematic risk before and during the Covid-19 pandemic. Keywords: Fundamental factors; systematic risk; stock return